Reducing Shrinkage and Stockouts in a Food Retail Store: A Portuguese Case Study - Marques, Pedro Alexandre; de Carvalho, André Mendes (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2021)
Lean thinking is transforming the traditional way of a retail business operates to new and more effective practices. In particular, the food retail business is facing previously unseen challenges which require daily operational excellence to meet them with success. Low productivity, high variability in task completion, lack of work planning should be faced with daily relentless improvement actions. Kaizen, the continuous improvement pillar of Lean, needs to be seen not only as a methodology but also as a philosophy, a vision that needs to be written on everyday actions and personified by each individual. This paper describes an improvement event in the fresh food markets, specifically in the cold meat section, meant to decrease the shrinkage rate as well as the number of out-of-stock (OOS) situations. The methodology adopted followed the seven-step problem-solving procedure provided by the A3 thinking tool.